2007
DOI: 10.1039/b613404a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of lanthanide(iii) complexes with bifunctional monophosphinic acid analogues of H4dota and comparative kinetic study of yttrium(iii) complexes

Abstract: New bifunctional H(4)dota-like ligands with three acetic acid and one phosphinic acid pendant arms and propionate (H(5)do3ap(PrA)) or 4-aminobenzyl (H(4)do3ap(ABn)) reactive groups bound to the phosphorus atom were investigated. Potentiometric studies showed that the ligands have a similar basicity to the parent H(4)dota and the stability constants of their complexes with sodium(i) and selected lanthanide(III) ions are also similar. Formation and acid-assisted decomplexation kinetics of yttrium(III) complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 82 publications
4
84
0
Order By: Relevance
“…The analogous redistribution of protons bound to ring nitrogen atoms as a consequence of the protonation of carboxylate/phosphorus acid pendant arms has been observed for other phosphorus-containing dota derivatives. [25,36,39] The protonation constants of the title ligand were determined by potentiometry, except for the first constant, which had to be determined from a dependence of 31 P{ 1 H} NMR spectroscopic chemical shift on Àlog [H + ] under controlled conditions. The protonation constants found for H 6 L are summarised in Table 1 and are compared with the values recently published by Kµlmµn et al [24] as well as with values found in the literature for similar ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analogous redistribution of protons bound to ring nitrogen atoms as a consequence of the protonation of carboxylate/phosphorus acid pendant arms has been observed for other phosphorus-containing dota derivatives. [25,36,39] The protonation constants of the title ligand were determined by potentiometry, except for the first constant, which had to be determined from a dependence of 31 P{ 1 H} NMR spectroscopic chemical shift on Àlog [H + ] under controlled conditions. The protonation constants found for H 6 L are summarised in Table 1 and are compared with the values recently published by Kµlmµn et al [24] as well as with values found in the literature for similar ligands.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the experimental crystallographic data is given in Potentiometric titrations: The stock/titration solutions of aqueous HCl ( % 0.03 m), NMe 4 OH ( % 0.2 m) and metal chlorides or nitrates used were the same as in previous studies. [36,39] Titrations were carried out in a vessel equipped with a thermostat at (25.0 AE 0.1) 8C, at ionic strength I = 0.1 m (NMe 4 Cl) and in the presence of extra HCl in the Àlog [H + ] range 1.7-11.9 (or until precipitation of a metal hydroxide) using a PHM 240 pH meter, a 2 mL ABU 900 automatic piston burette and a GK 2401B combined electrode (all Radiometer, Denmark). The initial volume was 5 mL and the concentration of the ligand was approximately 0.004 m. An inert atmosphere was ensured by constant passage of argon saturated with the solvent vapour.…”
Section: U(x)mentioning
confidence: 98%
“…HCl, % 0.03 m; NMe 4 OH, % 0.2 m) and metal chlorides or nitrates were the same as in previous studies; [52,53] the known amount of HCl was added to the stock…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[219]. Methyl hypophosphite was formed in situ and was reacted directly with methyl acrylate, affording, after hydrolysis, phosphinic acid 301 in 28% yield.…”
Section: Phosphinic Acids For Mri or Radioligand Deliverymentioning
confidence: 99%